(3GdeSJbUi aj CeKGd GdYQHs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3GdaVd Hf CHj GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CKdL Hg UOhQfG ef HQO Gdjbjf, hcSGg CYWGafG eJ JTQja GdESdGe s
(3BNQgG (B:s
(3YLJ fSGA Hfj RjGO YLI cYLjL fShJfG ZOGI GdCQfH ojhgj hdG jQbY(B: (3jVQH def ojaSoO hdG jUdM s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGX hGdRjGOGJ GdbdjdIs
(3Gdbde eged GdfbW CMjGfkG hHghGeTgG ebGHdGJ hJYdjbGJ hocJHJ GdCeKGd HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs